2011
DOI: 10.1111/j.1365-2516.2011.02585.x
|View full text |Cite
|
Sign up to set email alerts
|

UKHCDO guidelines on the management of HCV in patients with hereditary bleeding disorders 2011

Abstract: Summary. Chronic HCV infection continues to be of significant clinical importance in patients with hereditary bleeding disorders. This guideline provides information on the recent advances in the investigation and treatment of HCV infection and gives GRADE system based recommendations on the management of the infection in this patient group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 50 publications
1
9
0
4
Order By: Relevance
“…The management of these patients has been reviewed recently in the UKHCDO guidelines [10]. Patients coinfected with HIV and HCV have an approximately twofold greater risk of developing cirrhosis, and progress more rapidly to liver failure compared with HCV monoinfected individuals.…”
Section: Hiv/hcv Co-infected Patientsmentioning
confidence: 99%
“…The management of these patients has been reviewed recently in the UKHCDO guidelines [10]. Patients coinfected with HIV and HCV have an approximately twofold greater risk of developing cirrhosis, and progress more rapidly to liver failure compared with HCV monoinfected individuals.…”
Section: Hiv/hcv Co-infected Patientsmentioning
confidence: 99%
“…The availability of many methods of investigation offers the potential to follow patients with liver disease accurately and safely: laboratory, instrumental techniques, clinical history; liver function tests and platelet count should be performed twice a year; prothrombin time and α ‐fetoprotein once a year; transient elastography every 2 yr and ultrasound every 3 yr. Liver biopsy is the gold standard for diagnosis; the rate of clinically significant bleeding when performing liver biopsy can be minimised to 1–2% with adequate clotting factor coverage. The UK Haemophilia Centre Doctors’ Organisation (UKHCDO) has produced a set of guidelines for managing and treating PWH who have hepatitis C infection . A multicentre cohort study of antiviral therapy for 295 patients with haemophilia and hepatitis C infection has been carried out; the authors found that 119 patients achieved a sustained virological response after first treatment and an additional 28 patients were successfully retreated.…”
Section: Liver Complicationsmentioning
confidence: 99%
“…The importance of the need to treat hepatitis C virus infection in this patient group should therefore be emphasised. Guidelines for treatment have been recommended by the UKHCDO .…”
Section: Liver Complicationsmentioning
confidence: 99%
“…In around 20–30% of cases, HCV infection can progress to cirrhosis, culminating in end‐stage liver disease or hepatocellular carcinoma (HCC) [1]. Liver transplantation is the treatment of choice for patients with end‐stage liver disease as well as for those with small HCC [2]. The outcomes of liver transplantation in general are good with 1‐year survival approaching 90% and 5‐year survival reaching 75% in some centres [3].…”
Section: Viral Infection Of Donors and Their Suitability For Use In Lmentioning
confidence: 99%